Knjižnične storitve za slepe, slabovidne in za osebe z motnjami branja v sistemu slovenskih javnih knjižnic - Kodrič-Dačić, Eva (Knjižnica, 2011)
Purpose: Providing services to library users with special needs makes libraries for the blind and partially sighted different from other types of libraries. In spite of the Slovenian library act which defines them as special libraries providing public library service, they have not become a part of the public library system yet. The national program for culture issued by the Ministry of culture in 2008 stated that the solution should be proposed by the year 2011. Methodology/approach: The centre for library system development at the National and university library made an analysis of the current state and identified the weaknesses of the Slovenian library system and services for the blind. The solutions and best practices from abroad, national legislation and professional guidelines for libraries serving the blind were also explored. The concept of providing library services to the blind as public services was elaborated. Results: The centre for library system development suggested an integrated system with the central library providing library services i.e. reproduction of library materials in alternative techniques, and directing other libraries in providing services and developing new activities for the blind. Public libraries, already providing services to users with special needs should be encouraged to seek their own solutions. Originality/practical implications: The suggested concept of the national library for the blind is harmonized with the Slovenian library system and it could be realized with the cooperation of all the stakeholders involved.
Keywords: javne knjižnice; uporabniki s posebnimi potrebami; slepi; slabovidni; knjižnične storitve; Slovenia; Slovenija